Awareness of Cyber Crime on Social Media - GANESH, SOORYA; GANAPATHY, DHANRAJ; SASANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
More and more people, in spite of age and gender, are signing up for profiles on online social networks for connecting with one another during this virtual world. Some people have many friends and followers spread across multiple profiles. But at the same time there is proliferation of fake profiles also. Fake profiles often spam the users like posting inappropriate or illegal content. Fake profiles are created while misrepresenting some known person to cause harassment to him/her.This is a cross sectional study conducted among the common people through a questionnaire with 10 questions. The sample was taken on common people. The sample size of the study wass 100 and the results were tabulated accordingly.From the response collected it is evident that there is no significant relationship among the public regarding cyber crime. People who are associated with the IT sector are well aware than the general public on Cyber Crime. The Independent variable such as age and gender was taken into consideration and the dependent variable such as awareness about the ransomware and cyber crime was put forward to the public.The best of our knowledge, none of the previous researchers have adopted this approach.